A family claster of SARS-COV-!) infection - Todorović, Gordana; Joldic, Aleksandar; Andjelic, Sladjana; Nedeljkovic, Darko (Halo 194 Scientific Journal of Emergency Medicine, 2020)
Introduction We present the transmission of SARS-COV-2 within the family, in patients of different age groups, different sexes with the development of polymorphic clinical picture and objective status, but also different ways of infection. The range of symptoms ranged from malaise, loss of appetite without other ailments to fever, high fever, diarrhea, muscle and chest pain on inspiration. Dry, unproductive cough, shortness of breath, shortness of breath on exertion with sweating, headache and afebrile, characterized the third person, in whom bilateral pneumonia was also radiographically verified. Laboratory analyzes indicated SARS-COV-2 viral infection, which was confirmed by RT-PCR test in all three cases. After hospitalization and application of symptomatic, antiviral and antibiotic therapy, the disease regresses and tests are negative. Conclusion The described cases confirm the possibility of rapid infection within the family, directly and indirectly, as well as polymorphism of clinical picture, laboratory findings and objective status of patients.